The Implementation of Tahfiz Qur’an Juz 29 and 30 (Study in SD Islam Al-Mujahidin Cilacap) - Muhdir, Muhdir (International Conference of Moslem Society, 2016)
The background of this study the authors look at the implementation of programs of interest Tahfiz Elementary School. After examining various virtues and benefits of both the primacy of the world and the Hereafter, it is known that a great many virtues if Tahfiz be a program at the elementary school, there are still many elementary schools that have not implemented the program Tahfiz. From this background, giving a boost to the author to explore in order to reveal the subject matter regarding 1) how the implementation of the program Tahfiz Al-Quran Juz 29 and 30 in SD Islam Al Mujahidin Cilacap 2) how the factors supporting and hindering the implementation of programs in SD Islam Tahfiz Al-Mujahideen Cilacap. This study used qualitative methods, with the strategy case study. In this experiment the data collection process using the method of observation, interviews, and documentation. While the analysis used qualitative descriptive analysis technique. While the theory used in this research is the Program Implementation Tahfiz Al-Quran.Based on research that has been done, it is known how the implementation of the program Tahfiz Al-Quran Juz 29 and 30 in SD Islam Al Mujahidin Cilacap is good, because it has met some of the things that support the success memorize the Qur'an including curriculum program has become typical Tahfidz , Tahfidz programs implemented in class VI were allocated for 2 hours of lessons a week, this curriculum is developed independently. For children of sixth grade students are expected smoothly semeter I memorize Juz 29, while the second half is expected to smoothly memorize Juz 30. And there is an evaluation program every week, tests Tahfiz the end of each semester. From the memorization process is good then memorizing dihasilkanpun also be good, factors that affect the implementation of the program Tahfidz Qur'an grouped into two parts, namely supporting and inhibiting. Factor Tahfidz program supporting the Qur'an is the interest, motivation of students and teachers qiro'ah, while the factors inhibiting the implementation of the program Tahfidz Qur'an include; lack of skills in time management, lack of support from parents, and the environment.